Measuring And Reducing The Impact of Corruption In Infrastructure - Kenny, Charles (The World Bank, 2006)
This paper examines what we can say about the extent and impact of corruption in infrastructure in developing countries using existing evidence. It looks at different approaches to estimating the extent of corruption and reports on the results of such studies. It suggests that there is considerable evidence that most existing perceptions measures appear to be very weak proxies for the actual extent of corruption in the infrastructure sector, largely (but inaccurately) measuring petty rather than grand corruption. Existing survey evidence is more reliable, but limited in extent and still subject to sufficient uncertainty that it should not be used as a tool for differentiating countries in terms of access to infrastructure finance or appropriate policy models. The paper discusses evidence for the relative costs of corruption impacts and suggests that a focus on bribe payments as the indicator of the costs of corruption in infrastructure may be misplaced. It draws some conclusions regarding priorities for infrastructure anti-corruption research and activities in projects, in particular regarding disaggregated and actionable indicators of weak governance and corruption